Design and synthesis of cyclometalated iridium-based polymer dots as photocatalysts for visible light-driven hydrogen evolution. (13th November 2020) - Lin, Wei-Cheng; Elsayed, Mohamed Hammad; Jayakumar, Jayachandran; Ting, Li-Yu; Chang, Chih-Li; Elewa, Ahmed M.; Wang, Wen-Shin; Chung, Chih-Chia; Lu, Chia-Yeh; Chou, Ho-Hsiu
Abstract: The organic semiconducting polymer dots (Pdot) or nanoparticles exhibited a promising efficiency as photocatalyst for hydrogen production. This study reported a new Pdot-based photocatalyst constructed in the form of Donor-Acceptor-Metal cocatalyst (D-A-Mcat ). These D-A-Mcat Pdots systems consisting of fluorene (F) as the donor, thienyl-benzo-dithiophene-dione (TBDD) as the acceptor and [Ir (TPy)2 (acac)] as the metal complex, and their structural, thermal, electrochemical and photophysical properties were systematically demonstrated for the first time. Introducing the cyclometalated iridium (III) complex comonomer into the polymer chain resulting in PFTBDD-IrTPy Pdots showed enhancement of the hydrogen evolution rates, which is over 20-times higher than those of pure polymer (PFTBDD Pdots) under otherwise identical conditions. In addition, the optical and electrical measurements indicated that the cyclometalated iridium (III) part have an important function for inhibiting the charge recombination of the PFTBDD-IrTPy Pdots during the photocatalytic reaction. The result strongly implies that inserted catalytic amount of Ir(III)-complex into the D-A polymers is beneficial for the enhancement of photocatalytic hydrogen evolution, which can inspire further optimization and greater molecular design strategies at a low-cost are highly desirable for the development of high-performance in photocatalysis. Graphical abstract: Image 1 Highlights: Donor and acceptor with cyclometallic Ir-based polymer dots (D-A-Mcat Pdots) are developed for hydrogen evolution. The systematic study of PFTBDD-IrTPy Pdot of their thermal and photophysical properties are discussed. PFTBDD-IrTPy Pdot is a potential candidate for high HER activity as compared to PFTBDD Pdots. Introduction of Ir(III)-complex into the PFTBDD polymers is beneficial for the enhancement of photocatalytic activity.